A health fundraising experiment using the "foot-in-the-door" technique. Issue 3 (2nd July 2016) - Comello, Maria Leonora (Nori) G.; Myrick, Jessica Gall; Raphiou, April Little
ABSTRACT: Foot-in-the-door (FITD) involves obtaining compliance with a small request to boost compliance with a larger request. Only a few studies to date have tested the technique in health and fundraising contexts, and even fewer have examined the psychological processes involved. To address these gaps, we conducted an experiment as an actual fundraiser for a cancer-awareness organization. The technique activated a self-concept as a supporter of cancer awareness among those in the FITD condition. Donation amount was also higher among those in FITD, but only among those with higher levels of worry and low to moderate levels of preference for consistency.